SAVINGS AND INNOVATIVE TECHNOLOGIES IN IMPROVING AGRICULTURE AND WATER ECONOMY (World Bulletin of Social Sciences, 2025)
This article presents ideas and comments on specific solutions to the issues of saving and using innovative technologies in improving agriculture and water economy. The article also addresses issues such as water resource control, management technology, non-returnable waters. Various management methods are also recommended for achieving achievements in agriculture through saving water resources